A new species and a new subspecies of Euplexia Stephens, 1829 (Lepidoptera: Noctuidae: Xyleninae) from China - Gyulai, Péter; Ronkay, László (Zootaxa, 2018)
Two new taxa of the genus Euplexia Stephens, 1829 (s. str.), E. spica sp. n. (China, provinces Hunan, Gansu, Sichuan and Yunnan) and E. pali continentalis ssp. n. (China, provinces Shaanxi, Hubei and Sichuan) are described. This article presents a short taxonomic history, it also discusses the distribution pattern and relationships of Euplexia species occurring in Himalayan biotopes. The discussed items are illustrated with 34 figures.